THE LEGACY OF OUR GREAT ANCESTORS IS THE PRICELESS SPIRITUAL WEALTH OF OUR NATION (Archive of Conferences, 2020)
The article analyzes the role of the intellectual heritage of the great thinkers of Central Asia in the upbringing of a harmonious and comprehensively developed generation. The contribution of great scientists of the East to the development of world science and culture is presented